2005
DOI: 10.1026/0049-8637.37.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Der Rückschaufehler bei Kindern und Erwachsenen

Abstract: Zusammenfassung. Der Rückschaufehler (engl. “hindsight bias“) beschreibt die Tendenz, sich bei Schätzaufgaben durch vorgegebene Informationen systematisch beeinflussen zu lassen. Dieses Phänomen ist gut untersucht, allerdings ist seine entwicklungspsychologische Genese noch völlig unklar. Deshalb haben wir 274 Kinder und Erwachsene gebeten, die Antworten auf schwierige numerische Wissensfragen zu schätzen. Zu jeder Frage wurde ein niedriger oder hoher Wert als “Schätzung einer anderen Person“ (einer “Lehrerin“… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…Despite the substantial literature on hindsight bias that exists for adults, there has been little work on the developmental origins and trajectory of hindsight bias (but see Bernstein et al, 2004;Birch & Bernstein, 2007;Pohl & Haracic, 2005). This stands in stark contrast to the domain of theory of mind in which research has focused on developmental issues.…”
Section: Hindsight Biasmentioning
confidence: 84%
“…Despite the substantial literature on hindsight bias that exists for adults, there has been little work on the developmental origins and trajectory of hindsight bias (but see Bernstein et al, 2004;Birch & Bernstein, 2007;Pohl & Haracic, 2005). This stands in stark contrast to the domain of theory of mind in which research has focused on developmental issues.…”
Section: Hindsight Biasmentioning
confidence: 84%
“…As for children, given that the curse of knowledge appears to be stronger earlier in development (e.g., Birch & Bloom, 2003;Pohl & Haracic, 2005), it follows that younger children's performance on false-belief tasks would be more compromised than older children's and adults' performance. Note also that although we tested adults' curse-of-knowledge bias only in a displacement task (one of the tasks most commonly used to assess children's false-belief reasoning), the same logic can apply to a number of difficulties in mental-state reasoning when the subject has specific knowledge, such as the difficulties young children experience in unexpected-contents tasks (e.g., Perner et al, 1987), appearance-reality tasks (e.g., Gopnik & Astington, 1988), and source-of-information tasks (e.g., Taylor, Esbensen, & Bennett, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In earlier work (Birch & Bloom, 2003), we showed that 3-and 4-year-olds are more susceptible than 5-year-olds to a cognitive bias found in adults, the curse of knowledge (see also Bernstein, Atance, Loftus, & Meltzoff, 2004;Pohl & Haracic, 2005). We adopted this term from Camerer, Loewenstein, and Weber (1989) and use it to refer to the tendency to be biased by one's own current knowledge state when trying to appreciate a more naive perspective, whether that more naive perspective is one's own earlier perspective (as in the hindsight bias) or someone else's perspective (see Birch & Bernstein, 2007, for a discussion).…”
mentioning
confidence: 99%
“…For instance, Pohl and Haracic (2005) asked fourth, sixth, and eighth graders, as well as adults, to estimate the answers to difficult numerical knowledge questions. They were also provided with a value and told it was someone else's estimate, either a teacher's or a peer's, and were told not to let the other person's estimate influence their own.…”
Section: Changes In Hindsight Bias Across Developmentmentioning
confidence: 99%